Structural and Functional Plasticity of Antibiotic Resistance Nucleotidylyltransferases Revealed by Molecular Characterization of Lincosamide Nucleotidylyltransferases Lnu(A) and Lnu(D). Issue 12 (19th June 2015) - Stogios, Peter J.; Evdokimova, Elena; Morar, Mariya; Koteva, Kalinka; Wright, Gerard D.; Courvalin, Patrice; Savchenko, Alexei
Abstract: One of the main mechanisms of resistance to lincosamide and aminoglycoside antibiotics is their inactivation by O -nucleotidylyltransferases (NTases). Significant sequence variation of lincomycin nucleotidylyltransferase (Lnu) and aminoglycoside nucleotidylyltransferase (ANT) enzymes plus lack of detailed information about the molecular basis for specificity of these enzymes toward chemically distinct antibiotic scaffolds hinders development of a general strategy to curb this resistance mechanism. We conducted an extensive sequence analysis identifying 129 putative antibiotic NTases constituting six distinct subfamilies represented by Lnu(A), Lnu(B), Lnu(C), Lnu(D), Lnu(F)/(G) plus ANT(2″) enzymes. Since only the Lnu(B) enzyme has been previously studied in detail, we biochemically characterized the Lnu(A) and Lnu(D) enzymes, with the former representing the most sequence distinct Lnu ortholog. We also determined the crystal structure of the Lnu(A) enzyme in complex with a lincosamide. These data suggested that, while sharing the N-terminal nucleotidylyltransferase domain, the groups of antibiotic NTases feature structurally distinct C-terminal domains (CTDs) adapted to accommodate antibiotics. Comparative structural analysis among antibiotic NTases rationalized their specificity toward lincosamides versus aminoglycosides through active-site plasticity, which allows retention of general catalytic activity while accepting alterations at multiple, specific positions contributed by both domains. Based on this structural analysis, we suggest that antibiotic NTases evolved from an ancestral nucleotidylyltransferase along independent paths according to the identified groups, characterized by structural changes in the active site and recruitment of structurally diverse CTDs. These data show the complexity of enzyme-driven antibiotic resistance and provide a basis for broadly active inhibitors by identifying the key unifying features of antibiotic NTases. Graphical abstract: Highlights: Lnu O -nucleotidylyltransferases (NTases) confer resistance to lincosamides. Antibiotic NTases form six sequence-diverse groups. Lnu(A) structure reveals key molecular features conferring antibiotic specificity. Structural analysis shows that antibiotic NTases contain distinct CTDs. These findings illustrate the active-site plasticity of antibiotic NTases.